2012
DOI: 10.1155/2012/454717
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Use of Confocal Laser Endomicroscopy in the Bile Duct

Abstract: Background. Current methods to diagnose malignant biliary strictures are of low sensitivity. Probe-based confocal laser endomicroscopy (pCLE) is a new approach that can be used to evaluate in vivo histopathology of the GI tract. This paper is of studies evidencing pCLE's application in the diagnosis of indeterminate biliary strictures. Methods. This paper examined peer-reviewed studies conducted between January 2000 and November 2011. A PubMed search for relevant articles was performed using the following keyw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…17,[26][27][28] A review of the literature indicates that pCLE has been empirically superior to other optical imaging techniques. 12,14 A recent prospective study comparing narrow-band imaging, intrinsic autofluorescence, and pCLE for the diagnosis of gastric intestinal metaplasia using histology as the gold standard identified pCLE as the most accurate optical imaging technique. 17 Autofluorescence involves the sequential generation of an excitation light (370-470 nm) followed by a green light (540-560 nm), which then activates endogenous fluorophores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,[26][27][28] A review of the literature indicates that pCLE has been empirically superior to other optical imaging techniques. 12,14 A recent prospective study comparing narrow-band imaging, intrinsic autofluorescence, and pCLE for the diagnosis of gastric intestinal metaplasia using histology as the gold standard identified pCLE as the most accurate optical imaging technique. 17 Autofluorescence involves the sequential generation of an excitation light (370-470 nm) followed by a green light (540-560 nm), which then activates endogenous fluorophores.…”
Section: Discussionmentioning
confidence: 99%
“…12 High-contrast visualization is enabled through the injection of contrast agents such as fluorescein, which stain the surface epithelium extracellular matrix and allow structural and architectural comparison between surface mucosa and neoplastic tissue. 14 Probe-based confocal laser endomicroscopy has been used in Barrett's esophagus, gastric neoplasia, colorectal neoplasia, and bile duct lesions. 12,14,15 It is now FDA approved for the upper gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…Probe‐based confocal laser endomicroscopy (pCLE) is an emerging optical imaging technology that is rapidly being adopted by multiple disciplines for its ability to provide real‐time, in‐situ, histological visualization of tissue in the operating room. Described as an optical biopsy , pCLE produces magnified images that allow for the architectural comparison of normal cellular structure with neoplastic tissue through injected contrast agents, such as fluorescein, that stain the extracellular matrix of the surface epithelium . This technology has already seen use in the diagnosis and management of colorectal cancers, Barrett's esophagus, and biliary tract malignancies, with noted advantages including decreasing the number of biopsies, detecting tumor margins following resection, reducing cost, and allowing for immediate decision making …”
Section: Introductionmentioning
confidence: 99%
“…Described as an optical biopsy, pCLE produces magnified images that allow for the architectural comparison of normal cellular structure with neoplastic tissue through injected contrast agents, such as fluorescein, that stain the extracellular matrix of the surface epithelium. 1,2 This technology has already seen use in the diagnosis and management of colorectal cancers, Barrett's esophagus, and biliary tract malignancies, with noted advantages including decreasing the number of biopsies, detecting tumor margins following resection, reducing cost, and allowing for immediate decision making. 3,4 Head and neck cancer remains a major global health concern.…”
Section: Introductionmentioning
confidence: 99%
“…CLE generates images that elucidate cellular architecture and microvasculature at a level comparable to that achieved with traditional histology [11,12]. In particular, several studies have shown that this technology is useful for determining pathology in a variety of gastrointestinal tissue sites, including Barrett's esophagus [13][14][15], and lesions in the duodenum [16], colonic mucosa [17,18], and pancreatic biliary tract [19][20][21]. Moreover, it has been reported that CLE, incorporated into gastrointestinal endoscopy, is a useful approach for diagnosing various malignancies, including gastric [22,23], esophageal [24,25], colorectal [26,27], and pancreatic cancers [28].…”
mentioning
confidence: 99%